PENGARUH KUALITAS PELAYANAN TERHADAP BEHAVIORAL INTENTION (NIAT PERILAKU) PENGGUNA LIGHT RAIL TRANSIT (LRT) JABODEBEK - Rizka Meutia Ardita; Dyah Lituhayu (Journal of Management and Public Policy, 2026)
Jakarta is the center of national economic and educational activities thus playing a significant role in increasing commuter mobility in the Greater Jakarta area. High commuter activity has an impact on high levels of traffic congestion. Approximately 79.02% of people in the Greater Jakarta area choose to use private vehicles, while only 19.52% use public transportation. This situation causes significant economic losses, prompting the government to build the Jabodebek Light Rail Transit (LRT) as one of the National Strategic Projects to reduce congestion, discourage the use of private vehicles, and provide integrated public transportation in the Greater Jakarta area. However, after more than two years of operation, the Jabodebek LRT still faces various complaints regarding service quality that could potentially affect user satisfaction and behavioral intention. This study aims to analyze the influence of service quality on Behavioral Intention through Jabodebek LRT User Satisfaction. This is an explanatory research study with 100 respondents obtained through purposive sampling and convenience sampling. Data analysis was performed using SmartPLS4. The results of the study indicate that Service Quality has a positive and significant effect on User Satisfaction (β = 0.680), Service quality has a positive and significant effect on behavioral intention (β = 0.282), while user satisfaction has a positive and significant effect on behavioral intention (β = 0.546). The indirect effect of service quality on behavioral intention through user satisfaction is also proven to be significant (β = 0.371). Recommendations in this study include optimizing the signaling system, operating reserve trains during peak hours, improving station facility maintenance, improving the layout of directional signs, increasing the speed of communication regarding operational disruptions, improving employee responsiveness to complaints and emergency situations, proactively offering assistance, and developing a special complaint channel for Jabodebek LRT users.